In-plane doping profile control of plate-like organic single crystals grown by a method combining electrospray and low vapor pressure liquid film. (22nd February 2019) - Takeuchi, Keita; Ueda, Hiroyuki; Kikuchi, Akihiko
Abstract: Although the molecular doping of single crystal organic semiconductors is expected as a key technology that imparts attractive functions in optical and electrical properties, the doping technology in single crystal organic material is still in the initial stages. In this study, doping profile control in the organic single crystal was examined by using an organic single crystal growth method in which a low vapor pressure liquid thin film is used as a crystal growth field and solutes are supplied by electrospray deposition. Steep doping profile control with a transition region of around 1–2 μ m was demonstrated using dopants of small molecule red dye and green fluorescent polymer into plate-like single crystal of widegap fluorescent small molecule. We also evaluated the doping profile of the small molecule red dye in microwire-like single crystals of green fluorescent metal complex small molecule.